Nanotechnology in Veterinary Sciences: Magnetic nanosystems development based in functionalized iron oxide with silica and gelatine as theranostic agents (Veterinary Science, 2018)
Magnetic nanoparticles (MNPs) based on magnetite (Fe3O4)coated with silica find various applications in the field of biomedicalnanotechnology, due to their stability in aqueous medium.However, the inertia of the silica in terms of its reactivity limitsthe incorporation of specific functionalizers such as drugs andother ligands of interest. The challenge of this work focuses onobtaining biocompatible MNPs coated with silica and gelatin astheranostic agents in various biomedical fields, including veterinarymedicine. Photodynamic therapy represents an alternativeand a complement to chemo and radiotherapy, conventional tools for the treatment of different pathologies such as oncology.It consists of the use of photosensitive molecules that, when activatedwith light of a certain wavelength, transfer their excessof energy to neighboring oxygen molecules. This phenomenongenerates reactive oxygen species toxic to cells. Thus, the incorporationof a photosensitive agent to the magnetic silica nanoparticlesfunctionalized with gelatin would facilitate their specifictransport to the affected cells from the effect of an externalmagnetic field. This would result in a functional theranostic bothfor the diagnosis (by MRI) and for the treatment (phototherapy).In this work, various experimental conditions were exploredfrom MNPs of magnetite coated with citric acid and silicafor the deposition of gelatin from the co-precipitation method.An optimum formulation was obtained that was characterizedintegrally from the physicochemical point of view. As a photosensitivemolecule, methylene blue was selected and two routeswere explored for its incorporation into MNPs: 1-simple adsorptionfor 24 hours and 2-encapsulation. The evaluation of bothprocedures revealed the successful incorporation of the photosensitiveagent, obtaining magnetic nanosystems with potentialtheranostic properties applicable in the veterinary field.
Keywords: magnetic nanoparticles; silica; gelatin; theranostic for veterinary medicine